COVID-19 Lockdown’s Effect on Building Construction Projects in Kathmandu Valley Nepal - Bajracharya, Kreeti; Sukamani, Dinesh (SCITECH Nepal, 2023)
This research intends to assess the critical factors as an effect of COVID-19 lockdown on selected building construction projects within the Kathmandu Valley in Nepal. The research identifies “Health and Safety risk management” as the most critical factor compared to the other critical components namely supply chain operation, contractual and construction financial market. This research focuses on utilizing systematic partial least squares structural equation modeling to assess the effect of COVID-19 lockdown. Further, it seeks to demonstrate the direct relationships between COVID-19 effects and the critical factors that have been affected as a result of the pandemic. The study considers these factors as essential components in assessing the overall impact of COVID-19. This study attempts to evaluate and examine the significant pandemic effects on building construction projects. Nepal-based construction firms, government agencies, and non-government organizations were surveyed to identify critical factors affected by COVID-19 in building projects. The quantitative design method of this study included the use of smart partial least squares structural equation modeling (PLS-SEM), one of the statistical tools. Information like the fundamentals of the project, its state, etc., have been considered. 104 valid responses were received out of 130 questionnaires distributed supported at less than 1 % significance level. The inner structural model analysis, with a highest value of 7.014 and a beta value of 0.474, highlights the significance of the relationship between safety and risk management factors and COVID-19 effect in building construction projects. This relationship stands out as highly significant when compared to other constructs examined in the study. The findings underscore the crucial role of safety and risk management practices in mitigating the effects of the pandemic on construction projects.